Development and validation of a physical model to investigate the biomechanics of infant head impact. (July 2017) - Jones, M.; Darwall, D.; Khalid, G.; Prabhu, R.; Kemp, A.; Arthurs, Owen J.; Theobald, P.
Highlights: Impact produces regional and local accelerations up to 3× greater than "global". Differential acceleration very sensitive to impact location. Suture and fontanelle regions demonstrated 10× more strain than bone. Greater rotational velocities and accelerations produced, due to complex geometry. Abstract: Head injury in childhood is the single most common cause of death or permanent disability from injury. However, despite its frequency and significance, there is little understanding of the response of a child's head to injurious loading. This is a significant limitation when making early diagnoses, informing clinical and/or forensic management or injury prevention strategies. With respect to impact vulnerability, current understanding is predominantly based on a few post-mortem-human-surrogate (PMHS) experiments. Researchers, out of experimental necessity, typically derive acceleration data, currently an established measure for head impact vulnerability, by calculation. Impact force is divided by the head mass, to produce a "global approximation", a single-generalised head response acceleration value. A need exists for a new experimental methodology, which can provide specific regional or localised response data. A surrogate infant head, was created from high resolution computer tomography scans with properties closely matched to tissue response data and validated against PMHS head impact acceleration data. The skull was 3D-printed from co-polymer materials. The brain, represented as a lumped mass, comprised of an injected gelatin/water mix. High-Speed Digital-Image-Correlation optically measured linear and angular velocities and accelerations, strains and strain rates. The "global approximation" was challenged by comparison with regional and local acceleration data. During impacts, perpendicular (at 90°) to a surface, regional and local accelerations were up to three times greater than the concomitant "global" accelerations. Differential acceleration patterns were very sensitive to impact location. Suture and fontanelle regions demonstrated ten times more strain (103%/s) than bone, resulting in skull deformations similar in magnitude to those observed during child birth, but at much higher rates. Surprisingly, perpendicular impacts produced significantly greater rotational velocities and accelerations, which are closer to current published injury thresholds than expected, seemingly as a result of deformational changes to the complex skull geometry. The methodology has proven a significant new step in characterising and understanding infant head injury mechanics.